∫ 2 4 ln ( 9 − x ) + ln ( x + 3 ) ln ( 9 − x ) d x = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution.
The integral is continuous at [ 2 , 4 ] . Let I be the value of the integral.
( 9 − x ) and ( x − 3 ) go from 7 to 5 and from 5 to 7 as x g o e s f r o m 2 t o 4 respectively;
This symmetry allows us to use the substitution x = 6 − y ;
I = ∫ 2 4 l n ( y + 3 ) + l n ( 9 − y ) l n ( y + 3 ) d x ; ⟹
2 I = ∫ 2 4 l n ( x + 3 ) + l n ( 9 − x ) l n ( x + 3 ) + l n ( 9 − x ) d x = ∫ 2 4 d x = 4 − 2 = 2 ⟹
I = 1 .
Problem Loading...
Note Loading...
Set Loading...
Use ∫ a b f ( x ) d x = ∫ a b f ( a + b − x ) d x
W = ∫ 2 4 l n ( 9 − x ) + l n ( x + 3 ) l n ( 9 − x ) = ∫ 2 4 l n ( x + 3 ) + l n ( 9 − x ) l n ( x + 3 )
Adding the above two, we get :-
2 W = ∫ 2 4 d x
⟹ W = 1